A mechanochemical approach to access the proline–proline diketopiperazine framework - Pétry, Nicolas; Benakki, Hafid; Clot, Eric; Retailleau, Pascal; Guenoun, Farhate; Asserar, Fatima; Sekkat, Chakib; Métro, Thomas-Xavier; Martinez, Jean; Lamaty, Frédéric (Beilstein Journal of Organic Chemistry, 2017)
Ball milling was exploited to prepare a substituted proline building block by mechanochemical nucleophilic substitution. Subsequently, the mechanocoupling of hindered proline amino acid derivatives was developed to provide proline–proline dipeptides under solvent-free conditions. A deprotection–cyclization sequence yielded the corresponding diketopiperazines that were obtained with a high stereoselectivity which could be explained by DFT calculations. Using this method, an enantiopure disubstituted Pro–Pro diketopiperazine was synthesized in 4 steps, making 5 new bonds using a ball mill.
Keywords: ball mill; DFT calculations; diketopiperazine; mechanochemistry; pyrrolidine